STUDI KOMPARATIF MATA PELAJARAN KEWIRAUSAHAAN DI SEKOLAH MENENGAH ATAS (SMA) DAN SEKOLAH MENENGAH KEJURUAN (SMK) - Indah Dwi Lestari; Ambuy Sabur; Heni Cahya Ramdani (Universitas Islam Syekh Yusuf, 2020)
ABSTRACTUnemployment is still a problem for Indonesia. The level of open unemployment according to the highest institution dominated by Senior High School and Vocational High School graduates, therefore special handling is needed. The solution to overcome this problem is by increasing the amount of entrepreneurs by implementing entrepreneurship education at school. The specific purpose of this research is to dig out how the contents of the curriculum, process, assessment and advantages and disadvantages of entrepreneurship learning at SMA Negeri 5 and SMK Negeri 5 both located at Tangerang Regency in preparing prospective entrepreneurs. The research method used was a case study with a qualitative approach. The result showed that the curriculum content included competencies, teaching materials, and students’ learning experiences. The learning process includes the lesson plan (RPP) made by the teacher is in accordance with ministerial regulation. Student assessment of competency attitudes, knowledge and skills. Assessment was done by observation, oral test, written test and practical assessment. Based on the result of study it can be concluded that entrepreneurship learning in schools, viewed from the contents of the curriculum, process, assessment and strengths and weaknesses of entrepreneurial learning has led students to become prospective entrepreneurs.Keywords: curriculum content, learning process and assessment